Data from: Browsed twig environmental DNA: diagnostic PCR to identify ungulate species - Nichols, Ruth V.; Königsson, Helena; Danell, Kjell; Spong, Göran (Data Archiving and Networked Services (DANS), 2020)
Ungulate browsing can have a strong effect on ecological processes by affecting plant community structure and composition, with cascading effects on nutrient cycling and animal communities. However, in the absence of direct observations of foraging, species-specific foraging behaviors are difficult to quantify. We therefore know relatively little about foraging competition and species specific browsing patterns in systems with several browsers. However, during browsing, a small amount of saliva containing buccal cells is deposited at the bite site, providing a source of environmental DNA (eDNA) that can be used for species identification. Here we describe extraction and PCR protocols for a browser species diagnostic kit. Species specific primers for mitochondrial DNA were optimized and validated using twigs browsed by captive animals. A time series showed that about 50% of the samples will amplify up to 12 weeks after the browsing event, and that some samples amplify up to 24 weeks after browsing (12.5%). Applied to samples of natural browsing from an area where moose (Alces alces), roe deer (Capreolus capreolus), fallow deer (Cervus dama), and red deer (Cervus elaphus) are sympatric, amplification success reached 75%. This method promises to greatly improve our understanding of multispecies browsing systems without the need for direct observations. MER_Nichols2012_figure1_amplifiabilityThis data corresponds to Figure 1 within the publication entitled, 'Browsed twig eDNA: diagnostic PCR to identify ungulate species' published in Molecular Ecology Resources. Figure 1 is a model of how browsed twig environmental DNA degrades over time, represented by the total proportion of samples from moose, red deer and roe deer combined that amplified under our final PCR protocol. The data is separated into species. Samples were initially browsed by the above three species and then put on a fence to simulate natural conditions in the field and sampled at approximately 2 week intervals.